Design and synthesis of nanoscaled IQCA-TAVV as a delivery system capable of antiplatelet activation, targeting arterial thrombus and releasing IQCA - Wu J (Dove Medical Press, 2018)
Jianhui Wu,1,2,* Haimei Zhu,1,2,* Guodong Yang,1 Jianhong He,3 Yuji Wang,1,2 Shurui Zhao,1,2 Xiaoyi Zhang,1,2 Lin Gui,1,2 Ming Zhao,1,2,4 Shiqi Peng1,2 1Beijing Area Major Laboratory of Peptide and Small Molecular Drugs, Engineering Research Center of Endogenous Prophylactic of Ministry of Education of China, Beijing, China; 2Beijing Laboratory of Biomedical Materials, College of Pharmaceutical Sciences, Capital Medical University, Beijing, China; 3Department of Internal Medicine of TCM, The First Affiliated Hospital of Guanxi University of Chinese Medicine, Nanning, China; 4Department of Biomedical Science and Environmental Biology, Kaohsiung Medical University, Kaohsiung, Taiwan *These authors contributed equally to this work Background: Arterial thrombosis has been associated with a series of pathological conditions, and the discovery of arterial thrombosis inhibitor is of clinical importance. Methods: By analyzing the pharmacophores of anti-platelet agents, thrombus targeting peptide and anti-thrombotic nano-systems 3S-1,2,3,4-tetrahydroisoquino- line-3-carbonyl-Thr-Ala-Arg-Gly-Asp(Val)-Val (IQCA-TAVV) was designed and prepared as a nano-scaled arterial thrombosis inhibitor. Results: In vitro the nanoparticles of IQCA-TAVV were able to adhere onto the surface of activated platelets, attenuate activated platelets to extend pseudopodia and inhibit activated platelets to form aggregators. In vivo IQCA-TAVV targeted arterial thrombus, dose dependently inhibited arterial thrombosis with a 1 nmol/kg of minimal effective dose, and the activity was ~1670 folds of that of aspirin. Conclusion: IQCA-TAVV represented the design, preparation and application of nanomedicine capable of adhering on the surface of activated platelets, attenuating platelet activation, targeting arterial thrombus and inhibiting arterial thrombosis. Keywords: arterial thrombosis, thrombus targeting, nanodelivery, antithrombosis